Microbiological Study of Chronic Suppurative Otitis Media (Bangladesh Medical Journal, 2019)
Chronic suppurative otitis media (CSOM) is a prevailing and notorious infection in developing countries causing serious local damage and threatening complications. The purpose of the present study was determine the microbiological profile of isolates from discharge in CSOM. This study was conducted at out-patient department of ENT at Rajshahi Medical College Hospital, Rajshahi from January 2014 to December 2014. Samples were taken from 185 patients (both male and female) in all age groups suffering from chronic suppurative otitis media. Their Gram staining, culture, and biochemical tests were carried out to identify the organisms. It showed the predominance by staphylococcus aereus (29.13%), followed by Pseudomonas Aeruginosa (22.83%), Streptococcus Pyogen (14.96%), E.Coli (9.44%), Proteus Mirabilis (6.29%), Klebsiella Pneumonia ( 4.72%).Bangladesh Med J. 2017 May; 46 (2): 7-9